Vitamin D, intermediary metabolism and prostate cancer tumor progression - Wang, Wei-Lin W.; Tenniswood, Martin (Frontiers in Physiology, 2014)
Epidemiological data have demonstrated an inverse association between serum vitamin D3 levels, cancer incidence and related mortality. However, the effects of vitamin D on prostate cancer biology and its utility for prevention of prostate cancer progression are not as well defined. The data are often conflicting: some reports suggest that vitamin D3 induces apoptosis in androgen dependent prostate cancer cell lines, while others suggest that vitamin D3 only induces cell cycle arrest. Recent molecular studies have identified an extensive synergistic crosstalk between the vitamin D- and androgen-mediated mRNA and miRNA expression, adding an additional layer of post-transcriptional regulation to the known VDR- and AR-regulated gene activation. The Warburg effect, the inefficient metabolic pathway that converts glucose to lactate for rapid energy generation, is a phenomenon common to many different types of cancer. This process supports cell proliferation and promotes cancer progression via alteration of glucose, glutamine and lipid metabolism. Prostate cancer is a notable exception to this general process since the metabolic switch that occurs early during malignancy is the reverse of the Warburg effect. This “anti-Warburg effect” is due to the unique biology of normal prostate cells that harbor a truncated TCA cycle that is required to produce and secret citrate. In prostate cancer cells, the TCA cycle activity is restored and citrate oxidation is used to produce energy for cancer cell proliferation. 1,25(OH)2D3 and androgen together modulates the TCA cycle via transcriptional regulation of zinc transporters, suggesting that 1,25(OH)2D3 and androgen maintain normal prostate metabolism by blocking citrate oxidation. These data demonstrate the importance of androgens in the anti-proliferative effect of vitamin D in prostate cancer and highlight the importance of understanding the crosstalk between these two signaling pathways.